Currículo de língua portuguesa para surdos da Secretaria Municipal da Cidade de São Paulo: um estudo exploratório - Almeida, Thayná Carvalho de (Universidade Federal de São Carlos, 2021)
Aiming at the importance of bilingual education for the deaf and teaching PL as L2 for deaf people, a topic of great importance in the field of deafness, the present work aims to object of analysis the Portuguese Language Curriculum for the deaf in the city of São Paulo focusing on the literacy cycle (1st-3rd year of elementary school), with the objective of general: observe the articulation between the theoretical elements and the practical proposition of the Curriculum of the City Portuguese Language as a Second Language for the Deaf; and as a goal Specific: describe the role of the other in this document. It is a search qualitative, of a documentary nature, contrasting with the theoretical assumptions and practical, it was observed that there are discordant points in relation to these assumptions. It is expected that the present research will contribute to the proposition of future curricula still more harmonious in their formulations.
Curriculum of portuguese language for the deaf of the Municipal Department of the City of São Paulo: an exploratory study
Keywords: Currículos; Língua portuguesa; Surdos - Educação; Education - Curricula; Portuguese language; Deaf - Education; CIENCIAS HUMANAS::EDUCACAO::CURRICULO